The Growth and Distribution of Carcass Fat in Fattening Steer of Different Breeds - R Priyanto; R Johnson (Media Peternakan, 2012)
The growth and distribution patterns of carcass fat were investigated in three breeds of beef cattle entering fattening phase. The study involved 23 grass-fed steer Brahman, 24 Hereford and 22 Brahmanx Hereford crosses with a live weight range from 300-600 kg. An allometric Huxley model was used to study the growth and distribution patterns of fat tissue within wholesale cut. In most cases, Brahmans had significantly higher growth coefficients than Herefords and/or BrahmanxHereford crosses while Herefords and BrahmanxHereford crosses had similar growth coefficients in wholesale cuts. At log natural of 75 kg side muscle+bone weight (4.313 kg), Herefords had significantly a higher fat weight within wholesale cuts than Brahmans and BrahmanxHereford crosses. Comparison at log natural of 114 kg side muscle+bone weight (4.733 kg), whilst Brahmans and Herefords were similar in fat weight distribution, the cross-bred steer had lower fat weights than the other two breed groups in almost all wholesale cuts.